SURVEI SARANA DAN PRASANA PEMBELAJARAN PJOK SMP SE-KECAMATAN PINOH SELATAN - Enrico Febrianto; Nur Sulistyo Mutaqin; Nur Moh. Kusuma Atmaja (STKIP Melawi, 2022)
Abstract: This study aims to determine the planning, maintenance, treatment, elimination, sports facilities and infrastructure in junior high schools throughout Pinoh Selatan District. The research method uses qualitative. Data collection techniques using observation, interviews and documentation. The research instrument used observation sheets, interview sheets and documentation guidelines. Data analysis techniques include data reduction, data exposure, and drawing conclusions. The validity of the data using triangulation of sources and techniques. The results of the study at SMP Negeri 4 Satap Pinoh Selatan there were 13 types of sports facilities and infrastructure. At SMP Negeri 2 Pinoh Selatan there are 16 types of sports facilities and infrastructure. At SMP Negeri 5 Pinoh Selatan there are 13 types of sports facilities and infrastructure. At SMP Negeri 6 Pinoh Selatan there are 13 types of sports facilities and infrastructure. In the planning aspect, it is done by analyzing, planning, evaluating sports facilities and infrastructure. In the aspect of maintenance carried out by each teacher and student by cleaning learning tools after use. In the aspect of elimination by identifying, recording goods, making reports for facilities that cannot be used. The conclusion is that sports facilities and infrastructure in junior high schools throughout Pinoh Selatan District are good and suitable to be used to support the process of implementing sports and health physical education learning. Keywords: Facilities And Infrastructure, Learning, Physical Education Abstrak: penelitian bertujuan mengetahui perencanaan, pemeliharaan, perawatan, penghapusan, sarana dan prasarana olahraga di SMP se-Kecamatan Pinoh Selatan. Metode penelitian menggunakan kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Instrumen penelitian menggunakan lembar observasi, lembar wawancara dan pedoman dokumentasi. Teknik analisis data meliputi reduksi data, paparan data, dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi sumber dan teknik. Hasil penelitian di SMP Negeri 4 Satap Pinoh Selatan ada 13 jenis sarana dan prasarana olahraga. Di SMP Negeri 2 Pinoh Selatan ada 16 jenis sarana dan prasarana olahraga. Di SMP Negeri 5 Pinoh Selatan ada 13 jenis sarana dan prasarana olahraga. Di SMP Negeri 6 Pinoh Selatan ada 13 jenis sarana dan prasarana olahraga. Pada aspek perencanaan dilakukan dengan menganalisis, merencanakan, mengevaluasi sarana dan prasarana olahraga. Pada aspek pemeliharaan dilakukan oleh setiap guru dan siswa dengan membersihkan alat-alat pembelajaran setelah digunakan. Pada aspek penghapusan dengan mengidentifikasi, pencatatan barang, membuat laporan untuk sarana yang tidak dapat digunakan. Kesimpulannya adalah sarana dan prasarana olahraga di SMP se-Kecamatan Pinoh Selatan baik dan layak digunakan untuk mendukung proses pelaksanaan pembelajaran pendidikan jasmani olahraga dan kesehatan. Kata Kunci: Sarana dan Prasarana, Belajar, Penjasorkes